Application of mass spectrometry to elucidate the pathophysiology of Encephalitozoon cuniculi infection in rabbits. - Guillaume Desoubeaux; Maria Del Carmen Piqueras; Ana Pantin; Sanjoy K Bhattacharya; Roman Peschke; Anja Joachim; Carolyn Cray (PLoS ONE)
Encephalitozoon cuniculi is a microsporidian species which can induce subclinical to serious disease in mammals including rabbits, a definitive natural host. The pathophysiology of infection has not been comprehensively elucidated. In this exploratory study, we utilized two mass spectrometry approaches: first, the analysis of the humoral response by profiling the microsporidian antigens as revealed by Western blot screening, and second, implementing the iTRAQ®-labeling protocol to focus on the changes within the host proteome during infection. Seven E. cuniculi proteins were identified at one-dimensional gel regions where specific seropositive reaction was observed by Western blot, including polar tube protein 3, polar tube protein 2, and for the first time reported: heat shock related 70kDa protein, polysaccharide deacetylase domain-containing protein, zinc finger protein, spore wall and anchoring disk complex protein EnP1, and translation elongation factor 1 alpha. In addition, there was a significant increase of nine host proteins in blood samples from E. cuniculi-diseased rabbits in comparison with non-diseased control subjects undergoing various inflammatory processes. This included serum paraoxonase, alpha-1-antiproteinase F precursor and alpha-1-antiproteinase S-1 which have presumptive catalytic activity likely related to infection control, and cystatin fetuin-B-type, an enzyme regulator that has been poorly studied to date. Notably, 11 proteins were found to be statistically increased in rabbits with neurological versus renal clinical presentation of E. cuniculi infection. Overall, this novel analysis based on mass spectrometry has provided new insights on the inflammatory and humoral responses during E. cuniculi infection in rabbits.